Structural and Optical Properties of Chemically Deposited Metal Chalcogenide Thin Film CrS and its Photovoltaic Application - CHANDRASEKAR, J.; MANIKANDAN, DURGACHALAM (Asian Journal of Chemistry, 2022)
In this work, chromium sulfide (CrS) thin films were grown on the acetic acid substrates by chemical bath deposition to prepare non-toxic photovoltaic devices. The combined single-source precursor approach has been developed for the deposition method using tris(diethyldithiocarbamato)chromium(III) for the deposition of CrS thin films grown at bath temperatures of 30, 60 and 90 ºC and at a constant deposition time of 30-120 min. The sufrace mophology of the prepared films have been analyzed by SEM and HR-TEM techniques. The study of the films indicate the distributed roughness and nano bundled hexagonal structures. The energy dispersive X-ray (EDX) spectroscopy analysis conformed the presence of Cr and S. The polycrystalline behaviour of the films was studied by an XRD study which revealed the mixed phases with a predicted crystallite size of 20 nm. The optical measurements showed films had a maximum transmittance of 90% in the visible region and the evaluated energy band varied in the range of 2.2-2.378 eV with the change of bath temperatures. This suggests that CrS thin film prepared at 90 ºC has enhanced crystalline superiority. According to photoluminescence (PL) analysis, the green emission can be attributed to the presence of several deep trap states or defects in the CrS structure. Moreover, natural dye sensitized solar cells (DSSCs) in CrS thin film prepared at 90 ºC, Jsc (28.0 mA/cm2) produced a larger voltage in the short circuit as compared to synthetic dye sensitized solar cells (DSSCs) using CrS thin film Jsc (22.5 mA/cm2).